The Second Five Year Plan of the Indian Union 1956-1961 - Planning Commission (Planning Commission, 1958)
The Second Five Year Plan is intended to carry forward and accelerate the process of development initiated in the First Plan Period. The principal task is to secure an increase in national income by about 25 per cent over the five years, to take major strides forward in the direction of industrialization and to enlarge employment opportunities at a rate sufficient to absorb the increase in labour force consequent to the increase in population. The Second Five Year Plan is a continuation of the developmental efforts commenced in the First Plan but priorities have been shifted. There is now a larger accent on industrialization, especially the development of heavy industries and the necessary ancillaries like transport. The fulfilment of the tasks outlined in the Plan requires co-ordinated effort in both public and private sectors, but the role of public sector is the crucial one.
Ministry of Information and Broadcasting Government of India
Ministry of Information and Broadcasting Government of India